IMMEDIATE EFFECT OF MYOFASCIAL MANIPULATION IN HAMSTRING MUSCLE STRENGTH OF YOUNG WOMEN (Fiep Bulletin - online, 2011)
Introduction: The fascia can be divided into two types: superficial and deep. The deep fascia or myofascial involves the muscles and can capture and convey the tension produced by them. The continuous repetition of the same movement can cause densification of muscle fascia, but the external manipulation can restore the physiological conditions that tissue. Objective: To determine the immediate effect of the Fascial Manipulation © technique in hamstring muscle strength in young women. Materials and Methods: We conducted an analytical study, interventional, randomized clinical trial using a convenient sample, the variable studied was the hamstring muscle strength. The participants were randomly divided into two groups: intervention group (GI) and simulation of treatment group (GS). Initially both groups participted in the evaluation protocol, subsequently the GI went thru the intervention protocol and the GS thru the simulation protocol and then both were reassessed. Results: The study included 32 women. The GI showed an improvement in muscle strength and GS showed a reduction in muscle strength, but changes were not statistically significant for both groups. Discussion: The myofascial, when treated, is able to better perform its function. Therefore, myofascial manipulation would improve muscle strength. In this study we observed improvement but not significant statistically. Conclusion: It was a striking improvement of muscle strength immediately after application of the Fascial Manipulation© technique on young women, but not statistically significant.
Keywords: Fascia; Physical Therapy; Muscle Strength